Renal outcomes with sodium-glucose cotransporters 2 inhibitors - Sun, Xiaoya; Wang, Guohong (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) is one of the most serious complications of diabetes. Therefore, delaying and preventing the progression of DN becomes an important goal in the clinical treatment of type 2 diabetes mellitus. Recent studies confirm that sodium-glucose cotransporters 2 inhibitors (SGLT2is) have been regarded as effective glucose-lowering drugs with renal protective effect. In this review, we summarize in detail the present knowledge of the effects of SGLT2is on renal outcomes by analyzing the experimental data in preclinical study, the effects of SGLT2is on estimated glomerular flitration rates (eGFRs) and urinary albumin-creatinine ratios (UACRs) from clinical trials and observational studies, and renal events (such as renal death or renal failure requiring renal replacement therapy) in some large prospective cardiovaslucar outcomes trials. The underlying mechanisms for renoprotective activity of SGLT2is have been demondtrated in multiple diabetic and nondiabetic animal models including kidney-specific effects and secondary kidney effects related to amelioration in blood glucose and blood pressure. In conclusion, these promising results show that SGLT2is act beneficially in terms of the kidney for diabetic patients.